Notice: Payments for answers will end 4/10/2017. Click for more info.
You have new items in your feed. Click to view.
Question and answer
Q: Solve for x. -5x - (3x - 2) = 5 - 4(6x + 1) +17
A: -5x - (3x - 2) = 5 - 4(6x + 1) +17 -5x - 3x + 2 = 5 - 24x - 4 + 17 -8x + 2 = -24x + 18 -8x + 24x = 18 - 2 16x = 16 x = 1
Question
Asked 9/6/2010 1:36:28 AM
Updated 1/2/2015 8:56:58 AM
1 Answer/Comment
Get an answer
New answers
Rating
3
-5x - (3x - 2) = 5 - 4(6x + 1) +17
-5x - 3x + 2 = 5 - 24x - 4 + 17
-8x + 2 = -24x + 18
-8x + 24x = 18 - 2
16x = 16
x = 1

Added 1/2/2015 8:56:58 AM
This answer has been confirmed as correct and helpful.
Comments

There are no comments.

Add an answer or comment
Log in or sign up first.
27,011,782 questions answered
*
Get answers from Weegy and a team of really smart lives experts.
S
L
Points 254 [Total 272] Ratings 0 Comments 184 Invitations 7 Offline
S
L
R
Points 135 [Total 286] Ratings 1 Comments 5 Invitations 12 Offline
S
L
Points 130 [Total 130] Ratings 0 Comments 130 Invitations 0 Offline
S
R
L
R
P
R
P
R
Points 66 [Total 734] Ratings 0 Comments 6 Invitations 6 Offline
S
1
L
L
P
R
P
L
P
P
R
P
R
P
R
P
P
Points 62 [Total 13329] Ratings 0 Comments 62 Invitations 0 Offline
S
L
1
R
Points 34 [Total 1450] Ratings 2 Comments 14 Invitations 0 Offline
S
L
Points 10 [Total 187] Ratings 0 Comments 0 Invitations 1 Offline
S
Points 10 [Total 13] Ratings 0 Comments 10 Invitations 0 Offline
S
Points 10 [Total 10] Ratings 0 Comments 0 Invitations 1 Offline
S
Points 2 [Total 2] Ratings 0 Comments 2 Invitations 0 Offline
* Excludes moderators and previous
winners (Include)
Home | Contact | Blog | About | Terms | Privacy | © Purple Inc.